Interview with the Lead Designer Mike Laidlaw and Lead Writer David Gaider (and Lucas Christiansen) at BioWare about the Dragon Age games - Laidlaw, Mike (Gamevironments, 2016)
Interview with the Lead Designer Mike Laidlaw and Lead Writer David Gaider (and Lucas Christiansen) at BioWare about the Dragon Age games.